Age-related reference intervals for physical performance test outcomes relevant to male youth Middle Eastern football players - Lolli, L.; Gregson, W.; Bonanno, D.; Kuitunen, S.; Di Salvo, V. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To develop age-specific reference intervals for physical performance test outcomes relevant to male youth Middle Eastern football players. Methods: We analyzed mixed-longitudinal data (observations range: 1751-1943 assessments) from a sample of 441 male youth outfield football players (chronological age range: 11.7-18.4 y) as part of the Qatar Football Association and Aspire Academy development program over 14 competitive seasons. Semiparametric generalized additive models for location, scale, and shape estimated age-specific reference centiles for 10-m sprinting, 40-m sprinting, countermovement jump height, and maximal aerobic speed variables. Results: The estimated reference intervals indicated that the distribution of the physical performance test scores increased monotonically and nonlinearly with advancing chronological age for sprinting and countermovement jump outcome measures, reaching a plateau after 16 years common to each of these performance variables. The maximal aerobic speed median score increased substantially until ~14.5 years, with the nonlinear trend flattening off toward relatively older chronological ages. Conclusions: We developed age-related reference intervals for physical performance test outcomes relevant to youth Qatari football players. Country-wide age-specific reference intervals can assist in the longitudinal tracking of the individual players` progress over time against benchmark values derived from the reference population.